Um Framework para a gerência da disseminação adaptativa de mensagens de segurança em redes veiculares - Albano, Wellington Araújo (2015)
Vehicular networks (VANETs) are a type of self-organized ad hoc networks, in which the nodes are communication units present in the vehicle or in the road infrastructure. Currently, in research related to vehicular networks there is a great interest in safety-related services that aim at a collaborative traffic that will improve the safety of passengers. Most safety applications require sending data by broadcast, facing some difficulties such as the overhead to the network and other existing challenges in a wireless network environment. To address the problems found in the dissemination of broadcast messages, various proposals are available in the literature that aim to minimize the effect caused by the excessive number of messages, through strategies such as broadcast suppression and adaptation of communication parameters in situations that might compromise the delivery of messages. However, usually such proposals address the adjustment of local parameters such as the transmission power or the contention window size, without considering the overall effect of those adjustments on the network. To manage the way that adaptation is performed and to improve the performance of safety messages delivery, in this work we propose a framework composed of three modules: detection, prevention and adaptation. These three modules utilize information regarding connectivity conditions and network and traffic congestion which are shared with the neighboring vehicles. The proposed solution aims to fill a gap, contributing to manage the implementation of adaptation strategies in order to promote better performance for the dissemination of safety messages. Through simulation, we instantiate the framework in two case studies. At first, we simulate a scenario of an avenue in an urban area with variation in vehicle density. In a second case study, we use two scenarios in different situations. The results show that the application of the framework contributes to a better performance for safety messages dissemination regarding the delivery rate and the amount of sent messages, which are important metrics for this type of service that requires a high delivery rate to be efficient without causing network overhead. Despite the results, an investigation is required on other adaptation strategies such as controlling the transmission rate. The proposed framework, however, can be adapted for using components that address those issues. In addition, techniques different from those used in the modules present in the framework can be analyzed and other types of traffic can be evaluated. It is, therefore, a tool that can be exploited in other research situations.